2019
DOI: 10.3390/microorganisms7080235
|View full text |Cite
|
Sign up to set email alerts
|

Spectral Grouping of Nominally Aspergillus versicolor Microbial-Collection Deposits by MALDI-TOF MS

Abstract: Historical microbial collections often contain samples that have been deposited over extended time periods, during which accepted taxonomic classification (and also available methods for taxonomic assignment) may have changed considerably. Deposited samples can, therefore, have historical taxonomic assignments (HTAs) that may now be in need of revision, and subdivisions of previously-accepted taxa may also be possible with the aid of current methodologies. One such methodology is matrix-assisted laser-desorpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Several studies have shown that MALDI-TOF MS can be successfully used to identify fungi in this series. Recently, Reeve et al used MALDI-TOF MS technology to characterize 40 environmental isolates of Aspergillus series Versicolores [ 29 ]. They found consistent identifications with the Bruker database, identifying A. versicolor 2009_137364 MUZ and A. versicolor F51 LLH, which did not belong to the same spectral-linkage groups.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that MALDI-TOF MS can be successfully used to identify fungi in this series. Recently, Reeve et al used MALDI-TOF MS technology to characterize 40 environmental isolates of Aspergillus series Versicolores [ 29 ]. They found consistent identifications with the Bruker database, identifying A. versicolor 2009_137364 MUZ and A. versicolor F51 LLH, which did not belong to the same spectral-linkage groups.…”
Section: Discussionmentioning
confidence: 99%